Coexistent Squamous Cell Carcinoma and Granular Cell Tumor of Head and Neck Region: Report of Two Very Rare Cases and Review of the Literature. (February 2018) - Caroppo, Danila; Salerno, Grazia; Merolla, Francesco; Mesolella, Massimo; Ilardi, Gennaro; Pagliuca, Francesca; De Dominicis, Gianfranco; Califano, Luigi; Ciancia, Giuseppe; Russo, Daniela; Mascolo, Massimo
Granular cell tumor (GCT), a relatively rare neuroectodermal tumor occurring most often in the head and neck region, is not uncommonly associated with pseudoepitheliomatous hyperplasia of the overlying surface epithelium, which may be at times nonreadily distinguishable from well-differentiated squamous cell carcinoma (SCC). To the best of our knowledge, only a handful of coexisting SCC and GCT, mostly described in the esophagus, have been reported in (the current) literature so far. We herein report 2 new cases of coexisting GCT and SCC of the head and neck region, located, respectively, in larynx and tongue; comment on their clinical, imaging, and pathologic features; and discuss their management. In the present work, we also review the literature concerning this association to contribute to the head and neck pathologists' and surgeons' awareness regarding the possibility of this association for an adequate surgical excision and a better management of these patients.